Realizing women's rights to land and other productive resources - United Nations Entity for Gender Equality and the Empowerment of Women (UN Women) (2013)
The purpose of this publication is to provide detailed guidance for lawmakers and policymakers, as well as civil society organizations and other stakeholders, to support the adoption and effective implementation of laws, policies and programmes to respect, protect and fulfil women’s rights to land and other productive resources. It is based on the results of an expert group meeting held on 25-27 June 2012 in Geneva, Switzerland, during which papers were presented from various sectors and regions. These papers, and the discussions which were informed by them, helped to bring to the surface many of the critical issues facing women today in relation to the enjoyment of their land rights. The publication also incorporates additional case studies submitted by key experts, as well as extensive thematic research.